Prosiding ICOGISS 2019: International Confrence on Governance Innovation and Social Sciences 2019
DOI: 10.32528/pi.v0i0.2498
|View full text |Cite
|
Sign up to set email alerts
|

The Success Factors of Rural Community Based Tourism in Indonesia

Abstract: The practices showed that tourism has been recognized as a concept which contributes to local economic development. The research of Community Based Tourism was abundant but fails to provide detailed touching when it implemented at the rural level at developing countries. The paper attempt to enrich this discussion by providing key success factors of CBT's sustainable in five water objects tourism. A conceptual model from Thailand experience used as a basic framework and developed based on rural Indonesia conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
2
0
1
Order By: Relevance
“…319 de la misma Constitución, establece que se reconocen diversas formas de organización de la producción en la economía, entre otras las comunitarias, cooperativas, empresas públicas o privadas, asociativas, familiares, domésticas, autónomas y mixtas. Adicionalmente, es necesario conocer los factores que inciden positivamente (1-6) y negativamente (7-11) en la situación del turismo comunitario; según Sartika & Wargadinata, (2017) estos son: 1. Planificación participativa y desarrollo de capacidades para fortalecer las habilidades de gestión turística de la comunidad 2.…”
Section: Resultsunclassified
“…319 de la misma Constitución, establece que se reconocen diversas formas de organización de la producción en la economía, entre otras las comunitarias, cooperativas, empresas públicas o privadas, asociativas, familiares, domésticas, autónomas y mixtas. Adicionalmente, es necesario conocer los factores que inciden positivamente (1-6) y negativamente (7-11) en la situación del turismo comunitario; según Sartika & Wargadinata, (2017) estos son: 1. Planificación participativa y desarrollo de capacidades para fortalecer las habilidades de gestión turística de la comunidad 2.…”
Section: Resultsunclassified
“…The existence of community-based tourism becomes a pioneer of development in developing countries and provides more significant benefits for rural communities (Sartika & Wargadinata, 2019). Several cases in developing countries showed that:…”
Section: Community-based Tourismmentioning
confidence: 99%
“…Whereas in Dieng, Central Java, CBT can strengthen the social capital through awareness of tourism potential, combining traditional (local culture) and contemporary art into a tourism attraction (preservation and resilience) and developing mutual stakeholder cooperation for better communication (Sunuantari, 2017). Sartika and Wargadinata (2019) state that CBT must have ownership, participation, and responsibility to achieve success. Furthermore, CBT needs to integrate into several aspects, namely (1) Innovation in products and services, (2) Development of local community entrepreneurial skills, (3) Empowering local community leadership, 4) Support for infrastructure and accommodation at ecotourism destination areas, including the development of community-managed homestays based on local culture, and 5) Market-based promotional efforts from tourism stakeholders (Nugroho, Pramukanto, & Negara, 2016).…”
Section: Introductionmentioning
confidence: 99%